Mice Lacking GABAA Receptor δ Subunit Have Altered Pharmaco-EEG Responses to Multiple Drugs - Grotell, Milo; Abdurakhmanova, Shamsiiat; Elsilä, Lauri V.; Korpi, Esa R. (Frontiers in Pharmacology, 2021)
In the brain, extrasynaptically expressed ionotropic, δ subunit-containing -aminobutyric acid A-type receptors (δ-GABAARs) have been implicated in drug effects at both neuronal and behavioral levels. These alterations are supposed to be caused via drug-induced modulation of receptor ionophores affecting chloride ion-mediated inhibitory tonic currents. Often, a transgenic mouse model genetically lacking the δ-GABAARs (δ-KO) has been used to study the roles of δ-GABAARs in brain functions, because a specific antagonist of the δ-GABAARs is still lacking. We have previously observed with these δ-KO mice that activation of δ-GABAARs is needed for morphine-induced conditioning of place preference, and others have suggested that δ-GABAARs act as targets selectively for low doses of ethanol. Furthermore, activation of these receptors via drug-mediated agonism induces a robust increase in the slow-wave frequency bands of electroencephalography (EEG). Here, we tested δ-KO mice (compared to littermate wild-type controls) for the pharmaco-EEG responses of a broad spectrum of pharmacologically different drug classes, including alcohol, opioids, stimulants, and psychedelics. Gaboxadol (THIP), a known superagonist of δ-GABAARs, was included as the positive control, and as expected, δ-KO mice produced a blunted pharmaco-EEG response to 6 mg/kg THIP. Pharmaco-EEGs showed notable differences between treatments but also differences between δ-KO mice and their wild-type littermates. Interestingly mephedrone (4-MMC, 5 mg/kg), an amphetamine-like stimulant, had reduced effects in the δ-KO mice. The responses to ethanol (1 g/kg), LSD (0.2 mg/kg) and morphine (20 mg/kg) were similar in δ-KO and wild-type mice. Since stimulants are not known to act on δ-GABAARs, our findings on pharmaco-EEG effects of 4-MMC suggest that δ-GABAARs are involved in the secondary indirect regulation of the brain rhythms after 4-MMC.